8‐port multibeam planar UWB‐MIMO antenna with pattern and polarisation diversity. Issue 13 (31st July 2019) - Mathur, Rohit; Dwari, Santanu
Abstract : In this study, an 8‐port multibeam ultrawideband multi‐input–multi‐output (UWB‐MIMO) antenna having pattern and polarisation diversity is investigated for Wireless Personal‐Area Network access points. The proposed antenna consists of two different types of slot radiators, each of them provides four directive beams. The novelty of the proposed design is the achievement of a compact 8‐port UWB‐MIMO antenna using a common ground plane. Eight additional grounded slits are used in this design to enhance isolation. Antenna elements are placed in such a way that two adjacent antennas contribute different patterns. Results show that all the eight antenna elements cover complete UWB (3.1 to 10.6 GHz) with port isolation better than 15 dB. Proposed design offers gain better than 2 dB with envelop correlation coefficient lower than 0.1 from all ports.